A Paradigm Shift from Area-Led to Productivity-Led Production of Maize in Nigeria - M.S, Sadiq; I.P, Singh; M.M, Ahmad (Journal of Agriculture and Environmental Sciences, 2020)
Unlike in the past when production performance was judged from the area, in recent time’s growth performance is hinged on productivity. In Nigeria, increasing maize production through area expansion is no longer feasible owing to pressure on demand for arable limited land for allied sectors, urbanization, industrialization etc. thus threatening sustainable maize production which is the precursor for self-sufficiency in maize production. It is in lieu of this that the present research empirically examined the ex-post and ex-ante production trend of maize production in Nigeria. Time series data that spanned for 58 years (1961-2018) and covered production, area, yield and crop prices were used. The data were sourced from the FAO database and the collected data were analyzed using both descriptive and inferential statistics. The empirical evidence showed that maize production is not sustainable as area growth rate predominates in increasing the production growth rate of maize in the studied area. In addition, it was observed that variability in the production of maize owes majorly to uncertainty viz. weather vagaries. Furthermore, weather vagaries viz. drought and flood; and non-remunerative price of maize affected the supply response of maize. In a decade ahead, a deficit in the supply of maize is very imminent which will be owed to poor productivity, thus affecting the food security of maize in the studied area. Thus, the onus lies on the policymakers to invest adequately on technology and infrastructure in order to achieve a sustainable production of maize that will guarantee maize food security in the country.